Active aging program in nursing homes : effects on psychological well-being and life satisfaction - Buedo Guirado, Cristina (Colegio Oficial de Psicólogos de Madrid, 2020)
A great number of intervention strategies that provide opportunities to maintain physical, psychological, and social well- being have been carried out in order to promote active aging. Most of these strategies are aimed at people without physical or cognitive dependence, while institutionalized older people have not been considered as a target group. The main objective of this study was to analyze the effect of an active aging program on the psychological well-being and life satisfaction of institutionalized older people. A total of 141 participants with adequate psychomotor skills were selected (Mage = 85.50 years, SD = 8.47), and a quasi-experimental pretest-posttest design with a control group and an experimental group was used. The control group participated in the traditional limited active aging program offered in long-term care facilities - cognitive stimulation and physical activity - while the experimental group participated in a comprehensive active aging program. After the intervention, participants from the experimental group showed improvements in the mean values of psychological well- being and life satisfaction, while no change was found in the control group. The improvements in psychological well-being and life satisfaction were maintained 12 months later in the follow-up evaluation. This study suggests that the inclusion of a comprehensive active aging program in nursing homes, that comprises actions aimed at promoting empowerment, participation, and social openness, contributes to the maintenance of perceived well-being.